Laser micro-polishing for metallic surface using UV nano-second pulse laser and CW laser. Issue 9 (August 2016) - Pong-Ryol, Jang; Tae-Sok, Jang; Nam-Chol, Kim; Xing, Fu; kum-Hyok, Ji
Abstract During laser micro-polishing, the controllable laser energy density is a key technology to improve the surface roughness. In this paper, we have investigated a method which controls the energy density of ultraviolet (UV) pulse laser in real time with the control of continuous wave (CW) laser spot size in laser micro-polishing for metallic surface. The experimental and analytical considerations of several influence factors such as laser spot size, fusion zone, and focal offset were investigated. In addition, using a laser micro-polishing system manufactured with this method, the laser micro-polishing experiments on the two different surface shapes of stainless steel 316L were conducted. For the inclined or curved surface, the surface roughness improvements of up to 56.4 and 57.3 % were respectively obtained, and the analysis of the results were discussed.